Corrosion Resistance of High Strength Concrete Containing Palm Oil Fuel Ash as Partial Cement Replacement - Fadzil, Mat Yahaya; Khairunisa, Muthusamy; Nurhasshikin, Sulaiman (Maxwell Scientific Organization, 2014)
This experimental work investigates the influence of POFA as partial cement replacement towards corrosion resistance of high strength concrete. Plain high strength concrete (P0) with 100% ordinary Portland cement (control specimen) and POFA high strength concrete containing POFA as partial cement replacement material were used. At the first stage, mix with 20% POFA (P20) has been identified as the best performing mix after cubes (150×150×150 mm) containing various content of POFA as partial cement replacement were prepared, continuously water cured and subjected to compressive strength test at 28 days. At the second stage of study, control specimen (P0) and high strength concrete mix containing 20% POFA (P20) were prepared in form of cylinders with reinforcement bar buried in the middle for corrosion resistance test. Specimens were subjected to half cell potential technique following the procedures outlined in ASTM C876 (1994). Incorporation of POFA as partial cement replacement has contributed to densification of microstructure making the concrete denser thus exhibit higher resistance towards corrosion as compared to plain concrete.